Kirsten Gram Holmström: Monodrama, attitudes, tableaux vivants; studies on some trends of theatrical fashion 1770-1815. Tesis. Stockholm. (Uppsala), Almqvist & Wiksell (1967. 279 p. principalmente ilus. 2.2 x 15 cm. (Frent. port.: Acta Universitatis Stockholmiensis. Studies in theatrical History, 1). - Torres, Fanny (1969)
Fil: Torres, Fanny. Universidad Nacional de Cuyo